Evidence for the validity of a patient-based instrument for assessment of outcome after revision knee arthroplasty - Sabah, SA; Alvand, A; Beard, DJ; Price, AJ (British Editorial Society of Bone and Joint Surgery, 2021)
Aims: To estimate the measurement properties for the Oxford Knee Score (OKS) in patients undergoing revision knee arthroplasty (responsiveness, minimal detectable change (MDC-90), minimal important change (MIC), minimal important difference (MID), internal consistency, construct validity, and interpretability).